1992
DOI: 10.1530/acta.0.1270324
|View full text |Cite
|
Sign up to set email alerts
|

Serum parathyroid hormone-related protein concentrations in patients with hematologic malignancies or solid tumors

Abstract: S. Serum parathyroid hormone-related protein concentrations in patients with hématologie malignancies or solid tumors. Acta EndocrinolThe clinical significance of parathyroid hormone-related protein in humoral hypercalcemia of malignancy was investigated by determining the serum parathyroid hormone-related protein concentrations in 167 normal subjects, 56 patients with hematologic malignancy and 144 patients with solid tumor. Serum parathyroid hormone-related protein was measured with a radioimmunoassay kit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…However, even early stage breast cancers may be associated with aberrations in calcium homeostasis that are caused by parathyroid hormone-related protein (PTHrP), the agent of humoral hypercalcemia of malignancy [14]. Serum levels of PTHrP, which are known to increase serum levels of calcium, are reported to increase with tumor size in both hematologic and solid tumors [23]. However, if the increase in serum calcium that we observed were due to PTHrP, it might be expected that serum calcium levels would increase with tumor size and stage, which was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, even early stage breast cancers may be associated with aberrations in calcium homeostasis that are caused by parathyroid hormone-related protein (PTHrP), the agent of humoral hypercalcemia of malignancy [14]. Serum levels of PTHrP, which are known to increase serum levels of calcium, are reported to increase with tumor size in both hematologic and solid tumors [23]. However, if the increase in serum calcium that we observed were due to PTHrP, it might be expected that serum calcium levels would increase with tumor size and stage, which was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In one study (Firkin et al , 1996) PTHrP was elevated in 3/9 myeloma patients and 2/4 non‐Hodgkin lymphoma (NHL) patients with hypercalcaemia. Nakamura et al (1992) identified hypercalcaemia in 7/56 patients with haematological neoplasms. Of these seven patients, four (two with B cell NHL, one with adult T cell leukaemia and one with myeloma) had high serum PTHrP levels (Nakamura et al , 1992).…”
Section: Pathophysiologymentioning
confidence: 99%
“…These findings suggest that the normal leukocyte response to G-CSF affects serum LDH levels, while the serum PTHrP level may better reflect the status of the leukemia. Nakamura et al (12) have reported that the serum PTHrP concentration started to increase in parallel with tumor enlargement and before an increase in serum calcium. Our finding that elevation of the serum PTHrP concentration correlates better with leukemic cell proliferation than with serum calcium concentration indicates that serum PTHrP concentration may be useful in assessing disease status in leukemic patients with hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%